SWOT ANALYSIS OF REGIONAL RESILIENCE PLANNING: CASE STUDY OF MEDAN-BERASTAGI ROAD LANDSLIDE (PRAYER SPOT-SIBOLANGIT AND SIBOLANGIT -TONGKEH) - Feby Milanie; Abdiyanto; Adi Sabar Ginting; Hotler Tamba; Tony Sirait; Mhd. Ali Damanik; Anton Sahala Tua Banjarnahor; Daniel Horas Kristianto Siringoringo; Bety Zannatun (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to analyze landslide disaster resilience planning on Jalan Medan-Berastagi using the SWOT approach. The research method used is a case study with data collection through interviews, observations, and documentation. The results of the study indicate that landslide resilience planning on Jalan Medan-Berastagi needs to consider strengths, weaknesses, opportunities, and threats. Planning strategies that can be formulated based on the SWOT analysis include increasing coordination between agencies, adequate budget allocation, utilization of technology, increasing public awareness, development control, and adjustment of spatial plans. SWOT analysis is an effective tool in landslide resilience planning. Landslide resilience planning for the Medan-Berastagi Road needs to take into account existing strengths, weaknesses, opportunities and threats. Planning strategies that can be formulated based on SWOT analysis include improving coordination between agencies, adequate budget allocation, utilization of technology, increasing public awareness, development control, and adjusting spatial plans. Local governments need to improve coordination between related agencies in handling landslides, and allocate adequate budget for landslide mitigation activities. The use of new technology for landslide monitoring and prediction also needs to be optimized, as well as increasing public awareness of landslide risks through socialization and education activities. Development control in landslide-prone areas needs to be tightened, as well as adjustments to regional spatial plans that are adaptive to landslide risks. In the context of identifying types of disaster threats and estimating their impact on the surrounding environment, a study conducted in Sukoharjo Village showed that disaster threats include flooding and household waste, while in Prambon Hamlet and Nitikan Hamlet, the main threat is landslides. The development of sustainable landslide mitigation infrastructure also needs to consider ecological aspects, by integrating nature-based solutions such as land cover vegetation and natural drainage systems. It is important to note that risk identification must be carried out comprehensively by involving a thorough understanding of the project scope, design and specification analysis, and consultation with related parties.(Tinambunan, 2024).